We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
62
4
avatar

If there are vectors \(\mathbf{v} = \begin{pmatrix} 1\\2\\1 \end{pmatrix}, \mathbf{w} = \begin{pmatrix} 1\\4 \\5 \end{pmatrix}\) and \(\mathbf{x} = \begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix}.\) Find coefficients a, b, and c, not all 0, such that \(a\begin{pmatrix} 1\\2\\1 \end{pmatrix}+b \begin{pmatrix} 1\\4 \\5 \end{pmatrix} + c\begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix} = \begin{pmatrix} 0 \\ 0 \\ 0 \end{pmatrix}\)and answer with \(\dfrac{a-b}{c} \).

 Nov 3, 2019
 #1
avatar
0

One solution is a = 6, b = 2, c = 4, so (a - b)/c = (6 - 2)/4 = 1.

 Nov 3, 2019
 #2
avatar
0

Actually, a = 7k, b = 4k, c = k, so (a - b)/c = (7k - 4k)/k = 3.

 Nov 3, 2019
 #3
avatar+23516 
+2

If there are vectors \(\mathbf{v} = \begin{pmatrix} 1\\2\\1 \end{pmatrix}\)\(\mathbf{w} = \begin{pmatrix} 1\\4 \\5 \end{pmatrix}\),  and \( \mathbf{x} = \begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix}\).
Find coefficients a, b, and c, not all 0, such that

\(a\begin{pmatrix} 1\\2\\1 \end{pmatrix}+b \begin{pmatrix} 1\\4 \\5 \end{pmatrix} + c\begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix} = \begin{pmatrix} 0 \\ 0 \\ 0 \end{pmatrix}\)
and answer with \(\dfrac{a-b}{c}\).

 

\(\begin{array}{|lrcll|} \hline &\begin{pmatrix} 1&1&-1\\2&4&6\\1&5&15 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\\\ (2): &2a +4b+6c &=& 0 \quad | \quad : 2 \\ &a +2b+3c &=& 0 \\\\ &\begin{pmatrix} 1&1&-1\\1&2&3\\1&5&15 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\\\ (3) = (3) - (1) : &\begin{pmatrix} 1&1&-1\\1&2&3\\0&4&16 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\\\ (3) &0\cdot a +4b+16c &=& 0 \quad | \quad : 4 \\ & b+4c &=& 0 \\\\ &\begin{pmatrix} 1&1&-1\\1&2&3\\0&1&4 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\\\ (2) = (2) - (1) : &\begin{pmatrix} 1&1&-1\\0&1&4\\0&1&4 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\\\ (3) = (3) - (2) : &\begin{pmatrix} 1&1&-1\\0&1&4\\0&0&0 \end{pmatrix} \cdot \begin{pmatrix} a\\b\\c \end{pmatrix} &=& \begin{pmatrix} 0\\0\\0 \end{pmatrix} \\ \hline \end{array}\)

 

We set \(c=k\):

\(\begin{array}{|lrcll|} \hline (2): & 0\cdot a+1\cdot b+4 c &=& 0 \quad | \quad c=k \\ & b+4k &=& 0 \\ & \mathbf{ b } &=& \mathbf{ -4k } \\\\ (1): & 1\cdot a+1\cdot b- 1 \cdot c &=& 0 \quad | \quad c=k,\ b=-4k \\ & a-4k-k &=& 0 \\ & a-5k &=& 0 \\ & \mathbf{ a } &=& \mathbf{ 5k } \\ \hline \end{array} \)

 

proof:

\(\begin{array}{|rcll|} \hline a\begin{pmatrix} 1\\2\\1 \end{pmatrix}+b \begin{pmatrix} 1\\4 \\5 \end{pmatrix} + c\begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix} &=& \begin{pmatrix} 0 \\ 0 \\ 0 \end{pmatrix} \quad | \quad a=5k,\ b=-4k,\ c=k \\\\ \hline 5k\begin{pmatrix} 1\\2\\1 \end{pmatrix}-4k \begin{pmatrix} 1\\4 \\5 \end{pmatrix} + k\begin{pmatrix}-1 \\ 6 \\ 15\end{pmatrix} &=& \begin{pmatrix} 0 \\ 0 \\ 0 \end{pmatrix} \\\\ 5k-4k-k &=& 0 \checkmark \\ 10k-16k+6k &=& 0 \checkmark \\ 5k - 20k+15k &=& 0 \checkmark \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && \mathbf{ \dfrac{a+b}{c} } \\\\ &=& \dfrac{5k-(-4k)}{k} \\\\ &=& \dfrac{5k+4k}{k} \\\\ &=& \dfrac{9k}{k} \\\\ &=& \mathbf{9} \\ \hline \end{array} \)

 

laugh

 Nov 4, 2019
 #4
avatar+7747 
+1

\(a\mathbf{v} + b\mathbf{w} + c\mathbf{x} = \vec{0}\\ \begin{pmatrix} 1&1&-1\\2&4&6\\1&5&15 \end{pmatrix}\cdot\begin{pmatrix} a\\b\\c \end{pmatrix} = \begin{pmatrix} 0\\0\\0 \end{pmatrix}\\ \begin{pmatrix} 1&1&-1\\0&2&8\\0&4&16 \end{pmatrix}\cdot\begin{pmatrix} a\\b\\c \end{pmatrix} = \begin{pmatrix} 0\\0\\0 \end{pmatrix}\\ \begin{pmatrix} 1&1&-1\\0&1&4\\0&0&0 \end{pmatrix}\cdot\begin{pmatrix} a\\b\\c \end{pmatrix} = \begin{pmatrix} 0\\0\\0 \end{pmatrix}\\ \text{Let }c = k\\ b +4k = 0\\ \boxed{b = -4k}\\ a - 4k - k = 0\\ \boxed{a = 5k}\\ \dfrac{a - b}c = \dfrac{5k-(-4k)}{k} = 9\)

.
 Nov 4, 2019

11 Online Users

avatar
avatar